ANALISIS PENGARUH PDRB, SUKU BUNGA, TINGKAT INFLASI DAN KURS VALUTA ASING TERHADAP SIMPANAN MASYARAKAT PADA BANK UMUM DI KALIMANTAN BARAT - ME, YENNY HENDRA (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACTThis research intent to know PDRB'S influence, rate of interest, inflationrate and foreign currency rate to society trove (DPK) on public banks at WestKalimantan. Data type that is utilized as time series's data, taken from byStatistical Write-up Data of Bank Indonesia, namely of Write-up Quarterly up to 8years, of year 2004 2011, with data amount 32 moons. Analisis's tool that isutilized is analisis correlation and Multiple Regression, with OLS'S method, andClassical Assumsi Analisis. The Result observationaling to point out that: 1 ) PDRB (X1) havingpositive influence to DPK, pointed out by X1's regression coefficient as big as3.063. 2) Kurs of Dollar Rate point (X2) having positive influence to DPK, withX2's regression coefficient as big as 0.201. 3) Inflation Rates (X3) having positiveinfluence to DPK, with X3's regression coefficient as big as 0.001. 4) DepositosRate Zooms (X4) having negative influence to DPK, with regression coefficientas big as 0.002. Its mean each depositos rate ascension as big as 1% thereforesociety trove amount (Y ) experience decrease as big as 0.002 percent. The result count of simultan correlation, known by determinant coefficientpoint (R2) = 0,958. Its mean as a whole variation which happens on independentvariable (PDRB, Rate Of Interest zoom, Inflation rate) word or regarding oravailable simultan's relationship to dependen's variable (DPK) as big as 96%,meanwhile, its rest (4%) worded by other variable. Meanwhile of yieldingsignifikansi's quiz partial, known just PDRB that influential signifikan to DPK, ontrusty zoom 95%(? 5%). Its mean just PDRB that significant for developing tofoot up DPK on public banks at Time former Western. Meanwhile of yieldingsignifikansi simultan's quiz (Quiz f) conclude that variable fourth free (rDeposito,rTabungan, Rate, PDRB, Inflation) influential together signifikan to Dependent Variable (DPK).Key word : DPK, PDRB, Kurs Valuta Asing, Inflasi, Suku Bunga